2014
DOI: 10.1038/ejcn.2014.242
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength measurement as a predictor of hospitalization costs

Abstract: Low HGS at hospital admission is associated with increased hospitalization costs of between 16.6 and 20.0% after controlling for possible confounders, including undernutrition status. HGS is an inexpensive, noninvasive and easy-to-use method that has clinical potential to predict hospitalization costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…[ 12 ] Further studies are needed to clarify these results, given the importance of handgrip strength as a reliable parameter of several negative outcomes in the elderly. [ 35 , 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Further studies are needed to clarify these results, given the importance of handgrip strength as a reliable parameter of several negative outcomes in the elderly. [ 35 , 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…The Asian Working Group on Sarcopenia has recommended that sarcopenia should be assessed using both skeletal muscle mass and muscle strength, as well as physical function, such as handgrip strength [8]. Previous studies have reported that decreased muscular strength, such as handgrip strength, may be more associated with increased mortality, late-life disability, hospital admissions, cognitive decline, and poor quality of life in older adults [9][10][11][12][13] than skeletal muscle mass. However, current evidence focuses on skeletal muscle mass, with only a few studies demonstrating the association between muscular strength and cardiometabolic health in the US and Taiwan [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This is advantageous because it is easily and safely assessed in older people (Roberts et al 2011). Previous studies in older people have shown that decreased handgrip strength can predict adverse healthrelated events such as falls, disability, frailty, hospitalization costs, and mortality (Sallinen et al 2010;Xue et al 2011;Chen et al 2012;Guerra et al 2015), and it is commonly used as an objective measure of muscle strength in epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%